2009
DOI: 10.1088/0004-637x/694/1/367
|View full text |Cite
|
Sign up to set email alerts
|

The Clustering Behavior of Pre-Main-Sequence Stars in NGC 346 in the Small Magellanic Cloud

Abstract: We present evidence that the star-forming region NGC 346/N66 in the Small Magellanic Cloud is the product of hierarchical star formation, probably from more than one star formation event. We investigate the spatial distribution and clustering behavior of the pre-main sequence (PMS) stellar population in the region, using data obtained with Hubble Space Telescope's Advanced Camera for Surveys. By applying the nearest neighbor and minimum spanning tree methods on the rich sample of PMS stars previously discovere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 71 publications
(81 reference statements)
6
35
2
Order By: Relevance
“…This result agrees well with previous works, which also reveal hierarchically sub-grouped young stellar structures in individual star-forming regions (e.g. Schmeja et al 2009;Kirk & Myers 2011;Gouliermis et al 2014) or over the whole galaxies (e.g. Gouliermis et al 2010Gouliermis et al , 2015Gusev 2014).…”
Section: Group Identification and Dendrogramssupporting
confidence: 93%
“…This result agrees well with previous works, which also reveal hierarchically sub-grouped young stellar structures in individual star-forming regions (e.g. Schmeja et al 2009;Kirk & Myers 2011;Gouliermis et al 2014) or over the whole galaxies (e.g. Gouliermis et al 2010Gouliermis et al , 2015Gusev 2014).…”
Section: Group Identification and Dendrogramssupporting
confidence: 93%
“…Our results support the idea that stars in newly born clusters likely follow the fractal patterns of their parent molecular clouds, and that they eventually evolve towards more centrally concentrated structures (see Schmeja & Klessen 2006;Schmeja et al 2008Schmeja et al , 2009Sánchez et al 2007aSánchez et al , 2009). However, this seems to be only an overall trend.…”
Section: Discussionsupporting
confidence: 85%
“…In Testor et al (2005) a pure H 2 emission is detected in N88A at low spatial resolution, as well as along a north-south diffuse long filament at ∼6−8 to the east. In N66 (Henize 1956), which is a giant HII region in the SMC, Schmeja et al (2009) have reported that most of the H 2 emission peaks coincide with the bright component of the ionized gas and with compact embedded young clusters where candidate YSOs have been identified. Using SEST, Israel et al (2003) detected a CO molecular cloud of 1.5 × 1.5 in the region, reporting spectra and maps of the 12 CO lines J = 1−0 and J = 2−1.…”
Section: Introductionmentioning
confidence: 99%